Challenges and opportunities in pediatric surgery training in Germany: a view from the trenches - Sabine Drossard; Louisa Schuffert (BMC Medical Education)
Abstract Introduction Pediatric surgery training in Germany faces significant challenges related to structural issues and resource limitations, including variability in training sites and a lack of standardized oversight. This study aims to assess the current state of pediatric surgery training including its structure, quality, and resident satisfaction and identify areas for improvement. Materials and methods We conducted an online survey between May 2022 and November 2023 using single-choice, multiple-choice and open-ended questions. Additionally, information was gathered via analysis of available statistics and through direct contact with the State Chambers of Physicians. Results 75 pediatric surgery residents and 15 young specialists participated in the survey. 12 of 17 state medical chambers responded to our inquiry, but only 4 maintain detailed statistics. Training often extends beyond the planned six years, mainly (75%) due to insufficient surgical exposure. Residents reported a predominant role of attendings in surgical training and other residents in clinical training. They desired more involvement from chiefs in their education. A significant proportion (58.9%) noted a lack of dedicated scientific education. Nearly half (44.4%) of the respondents had changed training sites, primarily due to clinical rotations (26,7%) and dissatisfaction with training conditions (30,0%). Conclusion Pediatric surgery residents in Germany face inconsistent training quality and extended training periods, mainly due to insufficient surgical exposure. They report that some chiefs do not meet their obligations as trainers adequately. To address these issues, there is a need for enhanced oversight, standardized curricula, more surgical exposure and improved collaboration among training institutions.